Ion-transfer electrochemistry at arrays of nanoscale interfaces between two immiscible electrolyte solutions arranged in hexagonal format - Liu, Yang; Moshrefi, R.; Rickard, William; Scanlon, M.D.; Stockmann, T.J.; Arrigan, Damien (ELSEVIER SCIENCE SA, 2022)
The electrochemical behaviour of hexagonally arranged nanopore arrays was studied by simple ion transfer across the interface between two immiscible electrolyte solutions (ITIES) formed between water and 1,2-dichloroethane. The hexagonal nanoITIES arrays were supported at nanopores fabricated by focused ion beam milling into 50 nm thick silicon nitride films. Six arrays with different pore centre-to-centre distance (rc) to radius (ra) ratios were prepared. Within these arrays, the diffusion-limited steady-state currents (iss) of tetrapropylammonium cation (TPrA+) ion transfer increased concomitantly with increasing rc/ra ratio, reaching a plateau at rc/ra ≥ 96, which is greater than that previously reported for square-patterned nanoITIES arrays (rc/ra ≥ 56). The diffusion regime and iss associated with simple ion transfer across a nanopore array was also examined using numerical simulations, via COMSOL Multiphysics software, incorporating a 3-dimensional geometry and employing finite element analysis. Simulated linear sweep voltammograms of TPrA+ transfer demonstrated a unique diffusional behaviour dependent on hexagonal nanopore spacing and the rc/ra ratio, analogous to the experimental voltammograms. Overlay of simulated and experimental voltammograms for each rc/ra ratios showed good agreement. These results indicate that a new design criterion is required to achieve independent diffusion at hexagonal nanointerface arrays, in order to maximize nanodevice performance in electrochemical sensor technologies.